Analysis Impact Of Nursing Kpis And Electronic Medical Records On Service Quality In A Type B Hospital - Dwi Untari Fadillah Asih; Sholihul Absor; Mundakir (LP2IHKI UMSurabaya, 2025)
Objective : This study aims to analyze the effect of nursing Key Performance Indicator (KPI) implementation and Electronic Medical Record (ERM) utilization on service quality improvement in a Type B Hospital in Surabaya. Methods: This study employed a quantitative cross-sectional design involving 100 registered nurses selected through purposive sampling. Data were collected using a structured questionnaire consisting of 10 items for KPI implementation, 8 items for EMR utilization, and 12 items for service quality, measured using a 5-point Likert scale. Data were analyzed using multiple linear regression to examine the relationships between variables. Resulth : There was a considerable favorable impact on service quality from implementing KPIs (β = 0.427; p < 0.001), and ERM utilization also had a significant influence (β = 0.365; p < 0.001).The results highlight the importance of digital documentation systems and organized performance assessment in improving the quality of healthcare services. Conclusion : Healthcare services are made more efficient, accurate, and responsible by the combination of KPI and ERM.Based on the results of this research, healthcare facilities should enhance their performance management systems and maximize the use of health information technology in order to facilitate long-term quality improvement.